SITUATIONS PROBLEMS, NEEDS, AND GUIDELINES IN PHYSICAL EDUCATION LEARNING MANAGEMENT MODEL ON RHYTHMIC ACTIVITIES APPLYING PHENOMENON-BASED LEARNING APPROACH - Sukpattee, Pholphiphat; Kusolwong , Phanu; Prachanban, Sathin (Journal of Buddhist Anthropology, 2022)
The Objectives of this research were to investigate problem condition, needs, and guidelines in the physical education learning management model on rhythmic activities applying a phenomenon-based learning approach for secondary education. This study is qualitative research collecting data from 1) the interview of 8 teachers who have taught physical education, social studies, arts, and English subjects and a group discussion of 20 students enrolled in the rhythmic activities course from two secondary schools. This study further explores the problems and needs of physical education instruction in case of rhythmic activities integrated with social studies, arts, and English subjects using analytic induction and comparative analysis; 2) the interview of 5 experts using content analysis. The findings show that 1) the problems encompass the lack of objectives identifying the real-world applications and the 21st - century skills development, the lack of integration in terms of content and learning activities with other subjects, the shortage of learning materials for reviewing the steps, the inability to explain the content of rhythmic activities, the differences of the skills amongst the dancing partners, and the irresponsibility of task submission. 2) Needs include the identification of clear, measurable learning objectives pertinent to the 21st - century skills, the integration with other learning areas, the increase of practice time, explaining the understanding of societal contexts, gender, and learning differences, the accessibility of video clips for further study, and the collaborative assessment of the teachers and students focusing mainly on dancing skills and the 21st - century skills. 3) Guidelines for the learning management should focus on the conceptualization of the key competencies, the implementation of the learning activities integrated with contents on physical education, social studies, arts, and English subjects, the emphasis on the knowledge applicability, the usage of easily accessible learning materials, and on the collaborative assessment between learners and teachers.